Research on stem cell therapy for spinal cord injury: a bibliometric and visual analysis from 2018–2023 - Liu, Ruxing; Peng, Bo; Yuan, Jie; Hu, Jiahao; Yang, Jianxin; Shan, Nan; Li, Qichao; Zhao, Bin; Xu, Chaojian; Wang, Yongfeng (Frontiers in Genetics, 2024)
The aim of this study was to conduct a bibliometric analysis of the literature on stem cell treatment for spinal cord injury to gain an intuitive understanding of how the field is progressing, discover topics of interest, and determine what development trends are emerging in this field.greatest number of publications and citations are China, the Chinese Academy of Sciences, Dai JW, and the International Journal of Molecular Sciences, respectively.The top three high-frequency keyword clusters were hereditary paraplegia, reactive astrocytes and tissue engineering.With the help of visual analysis, we identified general trends and research topics of interest in the field of spinal cord injury over the last five years. Our findings suggest that stem cell transplantation for spinal cord injury and exosome therapy may be a focus of future research. This study provides a foundation for future research on stem cell therapy as well as clinical efforts in this field.Keywords Spinal cord injury, Stem cells, Tissue engineering, Bibliometric analysis, Exosome provided new hope for its treatment (5, 6). Stem cells can proliferate and self-renew under certain conditions and can further differentiate into multiple functional cells (7)(8)(9). This new research direction has attracted the interest of many researchers, and a large amount of related literature has emerged. However, among the vast number of studies, identifying the articles with significant value; the countries, institutions and authors making important contributions to the field; and the current topics of interest and future directions of development is an important challenge. To date, many published reviews and expert opinions have attempted to shed light on the current state and frontiers of research on stem cell therapy for SCI (10,11). However, these studies are relatively fragmented and subjective, insufficiently comprehensive or systematic, and less objective and quantitative, which is not conducive to obtaining an overall